2015
DOI: 10.3390/challe6010088
|View full text |Cite
|
Sign up to set email alerts
|

A New Compendium of Soil Respiration Data for Africa

Abstract: Abstract:The objective of this paper is to present to the scientific community a new dataset derived from existing literature on soil respiration in Africa. The data has thus been obtained by searching for records in peer review papers and grey literature. The main search engines used are: Scientific Citation Index (SCI) database, ISI Science web and Google scholar. This data description paper has greatly advanced the number of data points on soil respiration in Africa from 4 in 2010 to 62 in 2014. The new dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…[] did not provide new field Rs records, they appended SOC values for some Rs records. Additionally, Epule [] provided field Rs records from Africa. The data of Song et al .…”
Section: Methodsmentioning
confidence: 99%
“…[] did not provide new field Rs records, they appended SOC values for some Rs records. Additionally, Epule [] provided field Rs records from Africa. The data of Song et al .…”
Section: Methodsmentioning
confidence: 99%
“…Based on the SRDB, Bond-Lamberty and Thomson (2010a, 2010b) developed boreal-, temperate-, and tropical-specific empirical models to estimate global R S and analyze how R S responds to global warming. Building on the updated R S data in the SRDB are a new compendium of R S data for Africa (Epule, 2015), as well as field R S records from China (Song et al, 2014). Using the updated data, Zhao et al (2017) estimated R S for 10 biomes across the globe using artificial neural network models.…”
Section: 1029/2018ef000937mentioning
confidence: 99%
“…For instance, Raich and Potter (1995) analyzed the heterogeneity of R S response to environmental factors within three biomes (moist biomes with no dramatic dry season, biomes with a distinct dry season, and wetlands) and created three biome-specific models to estimate R SG . Building on the updated R S data in the SRDB are a new compendium of R S data for Africa (Epule, 2015), as well as field R S records from China (Song et al, 2014). Fortunately, the number of site R S measurements has increased substantially over the past several decades, and a continuously updated annual timescale global R S database (SRDB) was developed (Bond-Lamberty & Thomsom, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have synthesized the measurements of Rs at global and regional scales (Raich and Schlesinger, 1992;Raich and Potter, 1995;Raich et al, 2002;Bond-Lamberty and Thomson, 2010a;Chen et al, 2014;Epule, 2015). We added three currently available Rs databases (Bond-Lamberty and Thomson, 2014;Chen et al, 2014;Epule, 2015) together and found that the total number of Rs measurements by 2011 was 6147 globally, conducted at 1557 sites, with most of the measurements conducted in North America (but a few in Mexico), Western Europe, and East Asia (Fig.…”
Section: Spatial and Temporal Distribution Of Rs Measurementsmentioning
confidence: 99%
“…We added three currently available Rs databases (Bond-Lamberty and Thomson, 2014;Chen et al, 2014;Epule, 2015) together and found that the total number of Rs measurements by 2011 was 6147 globally, conducted at 1557 sites, with most of the measurements conducted in North America (but a few in Mexico), Western Europe, and East Asia (Fig. 2).…”
Section: Spatial and Temporal Distribution Of Rs Measurementsmentioning
confidence: 99%